Scotland's First 'National' History? Fordun's Principal Source Revisited. - Broun, Dauvit (Scottish Historical Review, 2024)
Fordun's principal source ('proto-Fordun') has been dated to 1285 based on assumptions that are challenged in this article. The material following Fordun's history in key manuscripts is investigated afresh as a survival of part of proto-Fordun. Proto-Fordun emerges as a seven-book work whose narrative may have reached as far as Edward I's conquest of 1304. It finished, however, with a series of documents relating to the case at the Curia in 1301 led by Baldred Bisset. At the heart of this analysis is prioritising the way this material is configured in the manuscripts, taking account particularly of all book-divisions, however confusing they may seem to be. It is suggested that proto-Fordun was probably composed in the late 1320s or 1330s. Superficially proto-Fordun could be regarded as Scotland's first 'national' history in the sense developed by Norbert Kersken in his study of similar works across Europe. It is suggested, however, that if our understanding of 'national' histories is determined chiefly by what is found in manuscripts (which can seem inconsistent and confusing) rather than by scholarly editions, then the development of 'national' histories can be seen (at least in a Scottish context) as an essentially organic process involving a range of authorial, editorial and scribal activity across generations, rather than solely about key works by individual authors.